The Influence of Work Environment and Work Engagement on Employee Performance Mediated by Employee Well-Being - Ni Kadek Dwi Ningsih Rabuana; Yanuar Yanuar (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to investigate the relationships between work environment, work engagement, employee well-being, and performance at PT. DBN. The study employs a quantitative approach using a descriptive research method. The population consists of employees from PT. DBN and a sample of 145 individuals were selected for analysis. Data analysis was conducted using the Smart PLS software version 3.0, utilizing a Partial Least Squares (PLS) test, which is a variant-based Structural Equation Modeling (SEM) approach. The research findings indicate that the work environment does not significantly affect employee performance at PT. DBN. However, a positive relationship exists between the work environment and employee well-being. Furthermore, work engagement has a positive impact on employee performance, and it also influences employee well-being positively. Employee well-being, in turn, demonstrates a significant influence on employee performance. Additionally, work engagement indirectly affects employee performance through the mediating role of employee well-being, as does the work environment. These findings contribute to a better understanding of the relationships between work environment, work engagement, employee well-being, and performance. They highlight the importance of creating a conducive work environment and promoting work engagement and well-being among employees to enhance overall organizational performance.